Exploration of the Psychological Elements in the Qur'an and Their Contribution to the Formation of Religious Character in Schools: A Literature Study - Andi Aziz; Aripuddin Aripuddin; Supriandi Supriandi (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
This research aims to identify and analyze the psychological elements contained in the Qur'an and their relevance to Islamic Religious Education (PAI). The study was carried out through the library research method by examining primary literature in the form of verses of the Qur'an, tafsir, and scientific works related to the psychology of Islamic education. The results of the study show that the Qur'an contains a number of psychological concepts that play an important role in the educational process, namely cognitive aspects (tafaqquh, tafakkur, dhikr, critical reason), affective (faith, patience, gratitude, compassion, fear and hope), and psychomotor (pious deeds, positive habits, behavior control). These three elements work integratively in shaping the personality character of students and directing the learning process that touches on mental, spiritual, and moral aspects. This study emphasizes that the use of Qur'an-based psychological principles in PAI learning can comprehensively increase students' motivation, religious awareness, and morals. These findings open up opportunities for the development of a PAI learning model that is more humanistic, holistic, and oriented towards the formation of Islamic personality.